The Complex Impact of Relational Embeddedness on Enterprise Value: The Moderating Effect of Environmental Dynamics - Hui Zhang (Discrete Dynamics in Nature and Society)
Based on social network theory and dynamic capability theory, a theoretical model is constructed that specifies the process through which relational embeddedness affects enterprise value. The authors selected 612 Shenzhen and Shanghai A-share manufacturing enterprises in the CSMAR database as sample enterprises, and a multiple regression analysis method was used to test hypotheses. The results show that (1) there is an inverted “U” relationship between relational embeddedness and enterprise value; that is, the enterprises’ relational embeddedness has an “inflection point” effect on the enterprise value; (2) the enterprises’ resource integration capability plays an intermediate role in the impact of relational embeddedness on enterprise value; (3) the market environmental dynamics and technology environmental dynamics play negative regulatory roles in the inverted “U” relationship between relational embeddedness and enterprise value, and they play different regulatory roles before and after the enterprise relational embeddedness reaches the “inflection point”; that is, before the relational embeddedness reaches the inflection point, the technology environmental dynamics plays a major negative regulatory role, while after the relational embeddedness reaches the inflection point, the market environmental dynamics plays a major negative regulatory role. Compared with the market environmental dynamics, the impact of technology environmental dynamics on the relationship between relational embeddedness and enterprise value is more significant; that is, the effect of relational embeddedness on enterprises value is more sensitive to the technology environmental dynamics.